A bionic paired hydrogen-bond strategy for extending organic π-conjugation to regulate emission. Issue 29 (22nd July 2021) - Ye, Guigui; Wang, Yigang; Hong, Liming; Yu, Fuqing; Xia, Guomin; Wang, Hongming
Abstract : We demonstrate a bionic hydrogen-bond strategy to extend the π-conjugation of organic fluorophores, from the perspective of spectral and theoretical analyses. Abstract : Herein, we first demonstrate a non-covalent strategy that extends the π-conjugation of fluorophores through bionic paired hydrogen-bond interactions. In well-designed molecular models, 1, 8-naphtholactam (Np)-equipped molecules (TPE/HTPE-Np) exhibit highly efficient dual-state emission in a red-shifted region, whereas their acenaphthene (Ap)-equipped counterparts (TPE/HTPE-Ap) reserve typical AIE behaviors with short-wavelength emission. Single-crystal and theoretical analyses prove that these bionic hydrogen-bond interactions enable the facile formation of dimeric TPE/HTPE-Np, resulting in their larger delocalized π-electron conjugation, thereby playing a crucial role in their unique emission characteristics.